PERAN KEPEMIMPINAN DIGITAL DANTON DALAM MENINGKATKAN PROFESIONALISME ANGGOTA DI BATALYON ARHANUD 3/YBY - Kuntarti, Rita; Fadhulurrahmadin, Fadhlurrahmadin; Putrantono, Asep Hanry (PPM Sdirjianbang Akademi Militer, 2025)
To create quality human resources, good leadership is essential. Therefore, organizations must be able to maintain and even enhance the professionalism of their members to achieve their stated vision and mission. Leaders play a strategic role in an organization, as without ideal leadership, there will be no constructive collaborative effort to achieve shared goals. The 3rd Air Defense Battalion/YBY is one of the spearheads in maintaining the air defense of the Republic of Indonesia (NKRI), requiring professional soldiers capable of coping with work pressures. This study aims to determine how digital leadership can enhance the professionalism of members within the 3rd Air Defense Battalion/YBY. The method used in this study is qualitative. The author, as the research instrument, obtained data through interviews with informants, observation, and document study. The results of this study indicate that the Danton's digital leadership role has not been optimally implemented within the 3rd Air Defense Battalion/YBY. This is evident in the lack of motivation and innovation among members in carrying out their duties within the unit. The implementation of Kodam protocol activities with high frequency, coupled with the continued apathy towards the main points of the leadership's wishes, exacerbates the obstacles in improving the professionalism of members in the 3/YBY Arhanud Battalion.